Fighting debt explosion in the European sovereign debt crisis: Eurobonds, leveraging EFSF and Euro-TARP - Aloys Prinz; Hanno Beck (Intereconomics, 2012)
A number of tools have been suggested for solving the European sovereign debt crisis, in particular the options of leveraging the EFSF/ESM, introducing Eurobonds and a European Troubled Asset Relief Programme (Euro-TARP). However, it is unclear how these instruments will work, given jittery financial markets, the pending sovereign default of Greece and the fear of contagion among other countries. In the following paper, these policy tools will be analysed and evaluated with respect to their effects as well as their potential power to solve the debt crisis.
Keywords: 330; Haushaltsdefizit; Öffentliche Schulden; Europäischer Stabilitätsmechanismus; Schuldenübernahme; Öffentliche Anleihe; Wirkungsanalyse; Haushaltskonsolidierung; EU-Staaten